Alpha event‐related synchronization after eye closing differs in Alzheimer's disease and dementia with Lewy bodies: a magnetoencephalography study. Issue 3 (8th February 2018) - Hata, Masahiro; Kurimoto, Ryu; Kazui, Hiroaki; Ishii, Ryouhei; Canuet, Leonides; Aoki, Yasunori; Ikeda, Shunichiro; Azuma, Shingo; Suehiro, Takashi; Sato, Shunsuke; Suzuki, Yukiko; Kanemoto, Hideki; et al.
Abstract : Background: The electroencephalography (EEG) abnormalities found in patients with dementia with Lewy bodies (DLB) are conflicting. In this study, we used magnetoencephalography, which has higher spatial resolution than electroencephalography, to explore neurophysiological features of DLB that may aid in the differential diagnosis. Methods: Six patients with DLB, 11 patients with Alzheimer's disease, and 11 age‐matched normal subjects were recruited. We investigated alterations in the ratio of event‐related synchronization (ERS) in the alpha band after eye‐closing. Results: Although the averaged ratio change of alpha ERS after eye‐closing appeared predominantly in the posterior brain regions in all study groups, DLB patients had the weakest ratio change of alpha ERS. In particular, DLB patients exhibited a significantly reduced ratio change of alpha ERS in the bilateral inferior temporal gyrus, right occipital pole, and left parieto‐occipital cortex compared to Alzheimer's disease patients or normal controls. Conclusion: Our findings indicated that a reduced ratio change of alpha ERS in the posterior brain regions elicited by eye‐closing is a brain electromagnetic feature of DLB.